The influence of tween 80 and polyethylen glycol 400 on piroxicam absorption from rat intestinal lumen in situ - Abdul Karim Zulkarnain; Arundita Kusumawida; Triani Kurniawati (Indonesian Journal of Pharmacy, 2008)
Oral drug absorption administered is highly influenced by dissolution rate, especially for poorly and insoluble drugs. Tween 80 and polyethylene glycol 400 (PEG 400) as surfactant an increase drug solubility by means of a micelle forming mechanism. The aim of the study wasto know the influence of addition and variation of Tween 80 and PEG 400 on the absorption of piroxicam from rat intestinal lumen in situ. Piroxicam solution in pH 7.5 phosphate buffer was prepared with the same concentration in three kinds based on the addition concentration of Tween 80 and PEG 400, they were 1.0, 1.5 and 2.0 % respectively. The male rats of 130-180 grams body weight fasted were for 24 hours before treatment. The rats were anaesthetized with 5x10-3 mL/g BW 40% urethan subcutaneously. Piroxicam unabsorbed fraction was measured in a spectrophotometer at 353 nm, and then calculate Papp (Appear Permeability). The data obtained were calculated according to Kolmogorov-Smirnov and one-way ANAVA then continued by a t-test (95% confidence level). Tween 80 at 10% and 1.5% increased piroxicam absorption from the phosphate buffer pH 7.5 but decreased with Tween 80 2.0%. According to Papp, thevalues were 0.3929 cm/minute (1.5% Tween 80), 0.3507 cm/minute (1.0% Tween 80) and 0.2593 cm/minute (2.0% Tween 80) respectively. PEG 400 at 2.0 % rised piroxicam absorption from the phosphate buffer pH 7.5 but no with influence PEG 400 1.5 % concentration one way ANAVA. Key words : Tween 80, Polyethylen glycol 400, piroxicam, in situ absorption